2013
DOI: 10.1245/s10434-013-3306-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Patients with Resectable Locally Recurrent Rectal Cancer After Total Mesorectal Excision with and Without Previous Neoadjuvant Radiotherapy for the Primary Rectal Tumor

Abstract: Surgical treatment of carefully selected patients with nonmetastasized resectable LRRC after nRTx and TME for the primary tumor is feasible and can result in sustained local control and overall survival. Patients with resectable LRRC who received nRTx for the primary tumor do not have a poorer outcome than patients who did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
1
32
1
2
Order By: Relevance
“…therefore, early diagnosis results in a better prognosis. 1,2 in most cases, the workup of a CRC recurrence includes an abdominal Ct scan or mRi and positron emission tomography scan. however, inflammatory changes around the anastomosis may mimic recurrence and turn out positive in the positron emission tomography scan.…”
mentioning
confidence: 99%
“…therefore, early diagnosis results in a better prognosis. 1,2 in most cases, the workup of a CRC recurrence includes an abdominal Ct scan or mRi and positron emission tomography scan. however, inflammatory changes around the anastomosis may mimic recurrence and turn out positive in the positron emission tomography scan.…”
mentioning
confidence: 99%
“…nine studies were found suitable for this study. 11,13,[15][16][17][18][19][20][21] in these studies, a total of 474 lRRC patients were treated after previous (chemo)radiotherapy and surgical resection for their PRC.…”
Section: Resultsmentioning
confidence: 99%
“…in 3 of 9 studies, irradiation therapy was composed of only radiotherapy (n = 146) 13,15,16 ; chemoradiation only was given in 3 studies (n = 124), [17][18][19] and in the remaining 3 studies, either radiotherapy (n = 103) or chemoradiation (n = 93) was given. 11,20,21 in most studies, eBRt for the primary tumor was given preoperatively in 2 studies, 11,20 either preoperatively or postoperatively in 3 studies, 18,19,21 and the timing of eBRt was undefined in 4 studies, 13,[15][16][17] (preoperative, n = 203; postoperative, n = 66; unknown, n = 197).…”
Section: Treatment Of Primary Rectal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Diğer taraftan %68 gibi yük-sek oranlara ulaşan ameliyat sonrası komplikasyon oranları bildirilmiştir. [7][8][9][10][11][12] Kemoterapi (KT) ve eksternal radyoterapi (EBRT) sadece palyatif fayda sağlamaktadır. [13][14][15][16] Konvansiyonel EBRT ile yüksek dozlara ulaşmak pelviste bağırsak ve mesane gibi normal dokuların doz sınırlayıcı etkisi nedeniyle riskli olabilir.…”
unclassified